Work Task Motivation, Emotional Intelligence and Public Leadership: Structural Equation Model on Organizational Culture - Maria Anabel Escosora; Eugenio S. Guhao, Jr (Camarines Sur Polytechnic Colleges, 2023)
This study was aimed to determine the best-fit model of organizational culture of public schools as influenced by work task motivation, emotional intelligence, and public leadership of school heads. The respondents of the study were the 403 teachers in Davao Region, Philippines, using correlational and structural equation modeling. The results showed that the levels of work task motivation, emotional intelligence of teachers, and organizational culture were very high while the public leadership of school heads was high. Further, all exogenous variables showed significant correlations with organizational culture.  Finally, findings showed Model 3 as the best fit-model. Model 3 revealed that work task motivation was described by its three remaining indicators, namely: introjected regulation, amotivation, and external regulation; while exogenous variable emotional intelligence  was measured by its two retained indicators, namely: self-awareness, and molivation; exogenous variable Public Leadership of School Heads was explained by its two remaining domains, naly: accountability leadership, and rule-following leadership. On the other hand, the endogenous variable organizational culture was described by its three retained indicators, namely: ta,oc, and km. This implies that in order to improve the school's organizational culture, the Department of Education may consider strengthening the retained indicators through their faculty development program.